Summer hot extremes and antecedent drought conditions in Australia. (23rd February 2022) - Páscoa, Patrícia; Gouveia, Célia M.; Russo, Ana; Ribeiro, Andreia F. S.
Abstract: The compound occurrence of extreme weather and/or climate events can cause stronger negative impacts than the individual events, and its frequency is increasing in several regions of the world. In this work, the effect of antecedent drought conditions on hot extremes during the months of December–February in Australia was analysed for two periods (1979–2019 and 1950–2019). The standardized precipitation evapotranspiration index (SPEI) and the indices number of hot days (NHD) and number of hot nights (NHN) were used to assess drought and extreme temperature events. While the link between dry and heat events is more important in the north in February, in December and January it is strong in the east coast. When temporal lags of 1–3 months are considered, there is a strong correlation between SPEI and NHD/NHN for the concurrent month on most of the study area. For the previous 1–3 months, the area and the correlation values decreased, but consistent spatial patterns were obtained for each month, namely negative correlations on the southwest and southeast in December, and the east in February. Tropical areas showed large areas of correlation between SPEI and NHN, including for the previous 3 months, whereas temperate climates showed the smaller area of correlation with NHN, including at the concurrent month. Significant correlations obtained for lead times longer than 1 month, namely with night heat extremes, point to a predictive ability in several regions of Australia. Moreover, the correlation coefficients obtained using the more recent period (1979–2019) show similar spatial patterns, but with higher values than for the 1950–2019 period. The results highlight the prospect of an early prediction of hot summer extremes in regions affected by drought in spring. Abstract : Strong correlation between SPEI and NHD/NHN for the concurrent month. For previous months, several regions exhibit statistically significant negative correlations. Tropical climates show largest areas of correlation between SPEI and NHN. Area of significant negative correlations between NHD/NHN and SPEI‐3, on the months of December–February, on each of the aggregated climate regions, and for a lag of 0 (concurrent) to 3 months, for the period 1979–2019.